A Centralized Algorithm with Collision Avoidance for Trajectory Planning in Preflight Stage. (7th January 2021) - Xiang, Zheng; Zhang, Wenqi; He, Deyang; Tang, Yu
Abstract : In order to better understand pretactical phase flow management with the flight plan centralized processing at its core, based on the flight plan centralized processing system and track-based operation, the aircraft's 4D trajectory planning challenges require a deeper level of analysis. Firstly, through establishing a flight performance prediction model, in which the flight plan data is extracted and the time when an aircraft passed a specified waypoint is calculated, a 4D flight prediction can be derived. Secondly, the air traffic flow of the waypoint is calculated, and a converging point along a flight route is selected. Through adjusting the time and speed of the aircraft passing this point, conflict between aircraft is avoided. Finally, the flight is verified by CCA1532, with the connecting flight plan centralized processing center set in line with the company's requirements. The results demonstrate that according to flight plans, the 4D trajectory of the aircraft can be predicted with the nearest minute and second, and the flow of a total of 20 aircraft within one hour before and after the passage of CCA1532 at key point WADUK can be calculated. When there is a conflict of 88 s between the convergence point and flight B, the speed of B aircraft is adjusted from 789 km/h to 778 km/h, and the time of passing the WADUK point is increased by 7 s, thereby realizing the conflict-free trajectory planning of the two flights.